Mid‐urethral slings in young, middle‐aged, and older women. Issue 8 (3rd September 2018) - Engen, Madeleine; Svenningsen, Rune; Schiøtz, Hjalmar A.; Kulseng‐Hanssen, Sigurd
Abstract : Aims: To compare subjective and objective outcomes of mid‐urethral sling (MUS) surgery in women in different age decades and the utilization rates for MUS in Norwegian women. Methods: Data from the national Norwegian Female Incontinence Registry on 21 832 women with stress or mixed urinary incontinence who underwent MUS surgery from 1998 to 2016 were used. Primary outcomes were treatment satisfaction and absence of objective stress leakage at 6‐12 months follow‐up and "MUS utilization rate." Secondary outcomes were increase in urgency incontinence symptoms and surgical complications. Results: Women in the sixth decade and older had more objective postoperative stress urinary leakage, and women in the seventh decade and older were less satisfied. Urgency incontinence symptoms (persistent and de novo) after MUS increased with age. Intermittent catheterization occurred significantly more often in the seventh decade and bladder perforation in the seventh and eighth decades. Women younger than the fifth decade had fewer complications, except the need for tape transection in the fourth decade. The "MUS utilization rate" increased in all age groups during the study period, but declined slightly in the oldest age group after 2010. Conclusion: All age groups had a high percentage of "very satisfied" and no objective stress leakage at 6‐12 months follow‐up, but declining slightly with age after the sixth decade. Urgency incontinence symptom bother increased with age, but the overall complication rates were low. Our study strengthens the argument that management of stress urinary incontinence with MUS seems suitable regardless of age.